Climate change regional review: Russia. (19th June 2013) - Sharmina, Maria; Anderson, Kevin; Bows-Larkin, Alice
Abstract : With climate change, an increasingly important focus of scientific and policy discourse, the Russian government has aimed to position the country as one of the leaders of the global process for addressing climate change. This article reviews a breadth of literature to analyze the politico‐economic situation in Russia with regard to international climate change negotiations, related domestic policies, societal attitudes, and climatic change impacts on Russia's territory. The analysis demonstrates how Russia has a pivotal role in influencing the future direction of international climate change mitigation and adaptation. Not only is Russia predisposed geographically to the impacts of climate change, but also it is a major emitter of greenhouse gases and a global supplier of fossil fuels, and remains a major force in international politics. This unique confluence of circumstances leaves Russia with a challenging dilemma. It can choose to acquiesce to short‐term political and economic considerations, adopt weak mitigation measures, and face potentially significant impacts. Or it can apply its considerable attributes and powers to initiate an epoch of international action to secure a low‐carbon climate‐resilient future. Although the former will see Russia subsumed into the international malaise on climate change, the latter may both quench the nation's 'thirst for greatness' and fill the void of international leadership. WIREs Clim Change 2013, 4:373–396. doi: 10.1002/wcc.236 This article is categorized under: Policy and Governance > National Climate Change Policy Trans‐Disciplinary Perspectives > Regional Reviews Trans‐Disciplinary Perspectives > National Reviews